The doctrinal detective in the interpretation of the statement statement of Sheikh Tabarsi (Tawhid, Justice, Imamate) as a model (Journal of the College of Basic Education, 2019)
In our research, we tried " The doctrinal detective in the interpretation of the statement statement of Sheikh Tabarsi (Tawhid, Justice, Imamate) as a model " to present the doctrinal mutation found in the folds of the Bayan interpretation; In order to graduate the study of this case, which I hope to have won, and I have neglected to mention the biography of Tabarsi, For repetition in more than one study, so I began the statement of doctrinal detective at the beginning of our research, from the unification and the completion of the imamate, It is worth mentioning that in this study we discussed the presentation of the doctrinal mutation found in the interpretation of the Bayan complex, and we left some of them because the research can not be used by the entire mabahith. It requires an independent academic study.I dealt with the first topic: the origin of the unification, and a branch of this origin, the study of several axes, the most important: the denial of the vision of God, and the occurrence of the Koran, The question of qualities.The second topic, entitled Justice, including: the obligation of kindness and righteousness and reform on God, and good and ugliness mental.And the last mabahith devoted to the imamate, which is the fourth origin of the religion of the imams of the imams, they can not believe them only believe in them.Then sealed search a conclusion outlined the most important outcomes of the research.